Isolation, Identification and Screening of Humic Acid Producing Fungi from Soil Environment of Oil palm (Elaeisguineensis) Associated with Empty Fruit Bunches - Hassan Musa Kawata; P F Omojasola; A E Ajiboye; M R Adedayo; Sheriffdeen Issa Bale (UMYU Journal of Microbiology Research)
The demand for sustainable and sustainable biotechnological processes has developed as a result of a growing interest in converting agricultural waste into valuable products. In this study, fungal strainswere isolated from soil environment ofoil palm empty fruit bunchesandscreened for humic acid production. In Osun state, Nigeria, soil sample was taken from a local palm oil mill. Different colonies of fungi were obtained for further research using the serial dilution plating procedure. Plate screening was used to evaluate the fungal biomass as well as colony diameter of the fungal isolates, and a submerged fermentation test was used to measure the amount of humic acid concentration the isolates produced. Fungal isolates were identified by using molecular methods and morphological analysis. The fungi species Aspergillusniger, Rhizopusstolonifer, and Penicilliumchrysogenum were isolated from the soil environment. When compared to Rhizopusstolonifer, Aspergillusniger grew more superiorly in terms of zone diameter (26.5 1.50 mm) and biomass (2.23 0.16 g), while Penicilliumchrysogenum showed no growth. Throughout the fermentation process, Aspergillusnigeralso produced a greater quantity of humic acid, with concentrations varying from 0.70 mg/l to 2.20 mg/l. Aspergillusniger strain HR18's existence was confirmed by molecular analysis. This experiment proved that Aspergillusniger can efficiently produce humic acid from OPEFB, providing a useful method for waste utilization and sustainable practices.